LOCAL WISDOM IN LARO NG LAHI AS FOUNDATION IN GAME-BASED PEDAGOGY - Roel V Avila (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2021)
Filipino traditional games (Laro ng Lahi) are reflective of the lifestyle of a locality and form part of significant national heritage. Albeit modern technology seems to challenge the existence of Laro ng Lahi, these traditional games can actually be transformed to adapt the present demands of the cyberspace. Employing the hermeneutic phenomenology and educational research development, the author paired the past investigations with his observations though the use of Hermeneutic Cycle as guide. Data obtained from the online survey accomplished by thirty-one (31) pre-service teachers (Generation Z, selected using the purposive sampling) provided connection between the online documents and the local practices and lived experiences of the respondents. Respondents are still familiar with piko (taplak gunung), agawan kuta (bentengan), and tubigan (gobak sodor) since they played such games before and they were aware of the the Laro ng Lahi benefits. Thus, they preferred to have Laro ng Lahi as activity tools in school subjects, and to convert academic knowledge and skills into learning course lessons. Upon finalizing the mechanics of each of the three Filipino traditional games, and the data provided by the respondents, the researcher conceptualized the game-based pedagogy and developed lessons using the local wisdom as the basis